New and Unexpected Insights into the Modulation of LuxR-type Quorum Sensing by Cyclic Dipeptides - O’Neill, Jennifer Campbell (2009)
Quorum sensing (QS) is under the control of N-acylated L-homoserine lactones (AHLs) and their cognate receptors (LuxR-type proteins) in Gram-negative bacteria, and plays a major role in mediating host-bacteria interactions by these species. Certain cyclic dipeptides (2,5-diketopiperazines, DKPs) have been isolated from bacteria and reported to activate or inhibit LuxR-type proteins in AHL biosensor strains, albeit at significantly higher concentrations than native lactones. These reports have prompted the proposal that DKPs represent a new class of QS signals, and potentially even interspecies or interkingdom signals; their mechanisms of action and physiological relevance, however, remain unknown. Here, we describe a library of synthetic DKPs that was designed to (1) determine the structural features necessary for LuxR-type protein activation and inhibition, and (2) probe their mechanisms of action. These DKPs, along with several previously reported natural DKPs, were screened in bacterial reporter gene assays. In contrast to previous reports, the native DKPs failed to exhibit either antagonistic or agonistic activities in these assays. However, non-natural halogenated cyclo(L-Pro–L-Phe) derivatives were capable of inhibiting luminescence in V. fischeri. Interestingly, additional experiments revealed that these DKPs do not compete with the natural lactone signal, OHHL, to inhibit luminescence. Together, these data suggest that DKPs are not QS signals in the bacteria examined in this study. Although these compounds can influence QS-regulated outcomes, we contend that they do not do so through direct interaction with LuxR-type proteins. This work serves to refine the lexicon of naturally occurring QS signals used by Gram-negative bacteria.